FEATURES OF THE INNOVATION PROCESS AT THE UKRAINIAN PHARMACEUTICAL ENTERPRISES - O. Chulak (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper deals with key theories of innovative process organization. Basic features of main stages of the innovative process on the pharmaceutical market of Ukraine are determined.